2013
DOI: 10.7860/jcdr/2013/6796.3594
|View full text |Cite
|
Sign up to set email alerts
|

“Neonatal Sepsis”: Bacteria & their Susceptibility Pattern towards Antibiotics in Neonatal Intensive Care Unit

Abstract: Background: Neonatal sepsis is one of the most common causes of neonatal mortality and morbidity, particularly in the developing countries. Its causative bacteria and their respective sensitivity patterns are different in each hospital and region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
45
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 14 publications
16
45
3
1
Order By: Relevance
“…Our findings were similar to the prevalence rate of 37.69% and 32% reported by Sharma CM et al and Gandhi S et al respectively from India. 12,13 This may be indicative of relatively similar management practices, hospital facilities and services provided. However, Jyothi P et al and Mhada TV et al reported lower prevalence of 19.2% and 24% respectively.…”
Section: Blood Culture Resultsmentioning
confidence: 99%
“…Our findings were similar to the prevalence rate of 37.69% and 32% reported by Sharma CM et al and Gandhi S et al respectively from India. 12,13 This may be indicative of relatively similar management practices, hospital facilities and services provided. However, Jyothi P et al and Mhada TV et al reported lower prevalence of 19.2% and 24% respectively.…”
Section: Blood Culture Resultsmentioning
confidence: 99%
“…This rate is lower than that reported in other studies. (2,3,13) Low isolation rates have also been reported in other studies. (14,15) Factors responsible for lower yield in blood culture in the presence of sepsis include inadequate volume of blood cultured, patients receiving antibiotics, inappropriate timing of culture, type of culture medium used, an inappropriate presumptive diagnosis and presence of other fastidious organisms or anaerobes.…”
Section: Discussionmentioning
confidence: 62%
“…(1) It has been seen that one in five neonates suffers from septicaemia in developing countries, which is responsible for 30-50% of total neonatal deaths annually. (2,3) Diagnosis based on clinical presentation alone is difficult due to non-specific presenting signs and symptoms. (4) The organisms causing neonatal sepsis and their antimicrobial susceptibility patterns are highly diverse and vary geographically, temporally and locally attributed to changing pattern of antimicrobial use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its incidence has been currently decreased thanks to advances in obstetric and neonatal care and intrapartum prophylactic antibiotic use to prevent development of perinatal Group B streptococcal infection, it is still an important problem of the newborn [2][3][4]. Inability of the susceptibility tests performed on culture media which are accepted as gold standard for the diagnosis of EONS, to rule out neonatal sepsis because of lack of bacterial growth despite isolation of the causative bacterial agent [5,6], in addition to limited specificity, sensitivity and reliability of diagnostic markers including WBC parameters (total WBC counts, absolute number of neutrophils, immature/total neutrophil ratio) and acute phase reactants (CRP and procalcitonin) have led to the development of scoring systems which use clinical and laboratory findings in combination for the diagnosis of EONS [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%